Melt-quenched porous organic cage glasses. Issue 35 (4th May 2021) - Brand, Michael C.; Greenwell, Francesca; Clowes, Rob; Egleston, Benjamin D.; Kai, Aiting; Cooper, Andrew I.; Bennett, Thomas D.; Greenaway, Rebecca L.
Abstract : The melting and glass-forming behaviour of a range of organic cages was investigated, with quenching of melted liquid states providing molecular glasses, one of which exhibited improved gas uptake compared to the starting amorphous cage. Abstract : The discrete molecular nature of porous organic cages (POCs) has allowed us to direct the formation of crystalline materials by crystal engineering. It has also been possible to create porous amorphous solids by deliberately disrupting the crystalline packing, either with chemical modification or by processing. More recently, organic cages were used to form isotropic porous liquids. However, the connection between solid and liquid states of POCs, and the glass state, are almost completely unexplored. Here, we investigate the melting and glass-forming behaviour of a range of organic cages, including both shape-persistent POCs formed by imine condensation, and reduced and synthetically post-modified amine POCs that are more flexible and lack shape-persistence. The organic cages exhibited melting and quenching of the resultant liquids provides molecular glasses. One of these molecular glasses exhibited improved gas uptake for both CO2 and CH4 compared to the starting amorphous cage. In addition, foaming of the liquid in one case resulted in a more stable and less soluble glass, which demonstrates the potential for an alternative approach to forming materials such as membranes without solution processing.